Risks and Strategies of China's Direct Investment in Central Asia from the Perspective of Big Data. (27th September 2022) - Huang, Jiong
Abstract : With the growth of Chinese economy and the improvement of its international status, Chinese enterprises foreign direct investment has ushered in new development opportunities. Although scale foreign investment continues to expand and has broad development prospects, it also faces huge risks that domestic investment has never had. China and Central Asia are highly complementary economically. Strengthening direct investment in the Central Asian countries can effectually drive China's economic development. Based on the quantitative evaluation and analysis from the perspective of big data, this paper uses a variety of methods to evaluate and explore the risks of China's direct investment in Central Asian countries, and gives some policy suggestions. The research shows that the motivation of Chinese foreign investment cooperation is different from the marginal industry transfer in the traditional international investment theory. The problem of country risks in Central Asia is prominent. Chinese government must rely on the build of the Belt and Road to strengthen intergovernmental communication and exchanges, and establish a good cooperation mechanism to deal with the increasingly prominent problem of country risks. Further we will improve trade facilitation and expand the trade openness of Central Asian countries to China. To avoid risks, Chinese companies should invest under the guidance of the government and establish a complete investment chain for large projects. At the same time, we also need to seize the opportunity of the development of digital economy, and gradually establish a scientific and efficient investment model to effectively avoid the risk of direct investment.